Peningkatan Disiplin Kehadiran Mengajar Guru Di Kelas Melalui Keteladanan Kepala Sekolah Di SD Inpres Wolooja 3 - Kristina Priyanti Embu (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
This research is School Action Research which aims to determine the improvement of teacher discipline in teaching attendance in the classroom through the example of the Principal at SD Inpres Wolooja 3, Wolowaru District, Ende Regency. The subjects of this study were teachers of SD INPRES Wolooja 3, Wolowaru District, 8 people. This research was conducted in the odd semester of the 2019/2020 school year. The results showed that the Principal's Example can improve teacher discipline in teaching attendance in class, where in the implementation of pre-cycle learning at the first meeting all teachers were present on time, because it was the first day of school for the 2019/2020 school year. The implementation of learning in the first cycle there were 4 teachers who were late to teach in class, and after the implementation of learning in the second cycle the teacher's discipline in teaching attendance in class reached 87.5% based on the responses of respondents (teachers) regarding the example of the Principal, while based on observations 37.5% Teachers who are still less than 5 minutes late.